Population Structure, Demographic History, and Adaptation of Giant Honeybees in China Revealed by Population Genomic Data. (17th February 2023) - Cao, Lianfei; Dai, Zhijun; Tan, Hongwei; Zheng, Huoqing; Wang, Yun; Chen, Jie; Kuang, Haiou; Chong, Rebecca A; Han, Minjin; Hu, Fuliang; Sun, Wei; Sun, Cheng; et al.
Abstract: There have been many population-based genomic studies on human-managed honeybees ( Apis mellifera and Apis cerana ), but there has been a notable lack of analysis with regard to wild honeybees, particularly in relation to their evolutionary history. Nevertheless, giant honeybees have been found to occupy distinct habitats and display remarkable characteristics, which are attracting an increased amount of attention. In this study, we de novo sequenced and then assembled the draft genome sequence of the Himalayan giant honeybee, Apis laboriosa . Phylogenetic analysis based on genomic information indicated that A. laboriosa and its tropical sister species Apis dorsata diverged ∼2.61 Ma, which supports the speciation hypothesis that links A. laboriosa to geological changes throughout history. Furthermore, we re-sequenced A. laboriosa and A. dorsata samples from five and six regions, respectively, across their population ranges in China. These analyses highlighted major genetic differences for Tibetan A. laboriosa as well as the Hainan Island A. dorsata . The demographic history of most giant honeybee populations has mirrored glacial cycles. More importantly, contrary to what has occurred among human-managed honeybees, the demographic history of these two wild honeybee species indicates a rapid decline in effective population size in the recent past, reflecting their differences in evolutionary histories. Several genes were found to be subject to selection, which may help giant honeybees to adapt to specific local conditions. In summary, our study sheds light on the evolutionary and adaptational characteristics of two wild giant honeybee species, which was useful for giant honeybee conservation.